PUBLIC RELATIONS STRATEGY ON RESPONDING ENVIRONMENTAL ISSUES TO SUSTAIN CORPORATE IMAGE: A Descriptive Study of Danone-AQUA's #BijakBerplastik - Noer, Mochammad Kresna; Megan, Deborah (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2020)
This study began with a contamination problem that was often brought up when speaking about environmental issues on a larger scale. The most debatable aspect of environmental issues nowadays is about marine plastic pollution that already contaminated the world's ocean. This issue then motivated societies in the world to start reducing plastic usage, but unfortunately, there are only a few companies that tried to support this movement. In Indonesia, Danone-AQUA is one of the companies that support the movement. In mid-2018, Danone-AQUA stated their commitment to engage in this said movement by making #BijakBerplastik commitment. This research was conducted using Cutlip and Center’s strategic public relations phase in understanding the social marketing effect that was done by Danone-AQUA in maintaining the positive image of the company as the pioneer of bottled drinking water in Indonesia. Using case study research method as its base with a post-positivistic paradigm and qualitative approach in descriptive nature, data was gathered by doing in-depth interviews and literature review studies. There are five key informants, two public relations communication consultants, representatives from Danone-AQUA, one public target, and one communications expert. This study found that the public relations strategy used by Danone-AQUA with the form of social marketing applied in #BijakBerplastik successfully maintains the corporate image in a positive way. To cite this article (7th APA style): Megan, D. & Noer, M. K. (2020). Public Relations Strategy on Responding Environmental Issues to Sustain Corporate Image: A Descriptive Study of Danone-AQUA's #BijakBerplastik. Journal Communication Spectrum, 10(1), 58-67. http://dx.doi.org/10.36782/jcs.v9i2.1984